Cancer dissemination from a physical sciences perspective. (13th June 2016) - Williams, Karla C; Wong, Eugene; Leong, Hon S; Jackson, Dwayne N; Allan, Alison L; Chambers, Ann F
Abstract: Cancer metastasis continues to be responsible for most cancer deaths. While much has been learned about molecular contributors to metastatic spread, the ability to effectively translate this knowledge to improved patient outcomes is still limited. Here we discuss various steps in the metastatic process from a physical sciences perspective, including hemodynamics pressure and forces in the circulatory system, sizes, half-lives and deformability of circulating tumor cells, physical aspects of cancer cell microvascular arrest, the role of adhesion and invadopodia in extravasation, and microparticles released by cancer cells during steps in metastasis. Awareness and improved understanding of the role of physical aspects of metastatic spread may offer new insights that may lead to new ways to better prevent, delay or treat metastatic disease.